2020
DOI: 10.3389/fphar.2020.00513
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric Adverse Events Associated With Infliximab: A Cohort Study From the French Nationwide Discharge Abstract Database

Abstract: The present retrospective, observational study confirmed that IFX treatment is associated with an elevated risk of psychiatric adverse events. Depending on the disease treated, physicians should be aware of these potential adverse events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 56 publications
0
19
0
1
Order By: Relevance
“…1). The evidence available regarding the manic or hypomanic induced by TNF‐α antagonists is limited to four case reports 17,22–24 and a cohort study 25 . Information about the patients, such as demographics, previous treatment, treatment response, manic or hypomanic adverse effects, and follow‐up time, were extracted and summarized in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…1). The evidence available regarding the manic or hypomanic induced by TNF‐α antagonists is limited to four case reports 17,22–24 and a cohort study 25 . Information about the patients, such as demographics, previous treatment, treatment response, manic or hypomanic adverse effects, and follow‐up time, were extracted and summarized in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…While infliximab has not been used for the adjunctive treatment of SZ or BD, a recent review examining the association between antibody immunotherapy for immune/inflammatory disorders and psychosis, found that 4 out of 8 antibody therapies suppressing TNF (including infliximab) correlated with a decreased risk of psychosis 71 . However, cases describing acute psychosis after the administration of TNF antibody therapy have also been reported 72,73 . Piroxicam has not been used as an adjunctive treatment for SZ or BD, but studies of non-selective COX inhibitor (aspirin) and selective COX-2 inhibitor (celecoxib) in SZ 74,75 have reported symptomatic improvement in SZ patients, with the greatest benefit during a first episode of psychosis 76 .…”
Section: Discussionmentioning
confidence: 99%
“…Within days of the first infliximab infusion, he experienced symptoms of depression, which intensified over weeks and resulted in a serious suicide attempt. 7 In a cohort study analyzing data from the French national hospital higher risks were observed for certain pairs of adverse events and underlying pathologies: psychotic disorders in patient treated for ulcerative colitis, manic episodes in patients treated for severe psoriasis, and suicide attempts in patients treated for rheumatoid arthritis. 8 Infliximab neutralizes the biological activity of TNF-α by binding with high affinity to the soluble (free floating in the blood) and transmembrane (located on the outer membranes of T cells and similar immune cells) forms of TNF-α, and inhibits or prevents the effective binding of TNF-α with its receptors.…”
Section: Discussionmentioning
confidence: 99%